The Third Function of Law Is to Transform Cultural Categories - Hoff, Karla; Walsh, James (World Bank, Washington, DC, 2019)
How does law change society? In the rational actor model, law affects behavior only by changing incentives and information -- the command and coordination function of law. Under the view that humans are social animals, law is also a guidepost for social norms that regulate behavior -- the expressive function of law. This paper proposes a third function of law—the schematizing function -- based on cognitive research that shows that individuals cannot think without categories. Law makes possible new kinds of exemplars, role models, and social interactions that give people prototypes that transform the categories they use, thereby reframing their options and influencing their behavior. This paper illustrates the schematizing power of law with examples from field and natural experiments. Like the one-two punch in a boxing match, the command and schematizing functions of law together can change society in situations where the command function alone would be ineffective or backfire.